Avaliação da densidade populacional e seleção de microhabitats em passeriformes florestais na RPPN Mata do Cedro, Rio Largo, AL, Centro de Endemismo Pernambuco - Prado, Luiza Carvalho (2021)
The Pernambuco Endemism Center (PEC) is an area of Atlantic Forest with high biodiversity levels due to biogeographic and historical factors. Located in Northeastern Brazil, north of the São Francisco River, the PEC is considered one of the most threatened regions on earth, being the most fragmented and degraded Atlantic Forest area in the entire biome. The PEC houses a series of endemic and endangered species, some of which are still in the process of being described. The classification of the levels of threat of the animals from the PEC in red lists have been based solely on their geographic distribution and areas of occurrence, especially because data on population density and population size estimates are unavailable. These estimates, when associated with studies on habitat selection and preference, can provide conservation managers with important information, useful to decide where and how to direct resources and efforts for conservation. In this work, population censuses estimates were carried out for five passerine species in one of the most representative PEC fragments from the state of Alagoas, using Distance sampling linear transects. All of the species are threatened with extinction and endemic to the PEC: the Pernambuco Fire-eye Pyriglena pernambucensis (VU), the Black-cheecked Gnateater Conopophaga melanops nigrifrons (VU), the White-shouldered Antshrike Thamnophilus aethiops distans (EN), the Brown-winged Mourner Schiffornis turdina intermedia (VU), and the White-bellied Tody-tyrant Hemitriccus griseipectus naumburgae (VU). Although four of the five taxa are included in the same threat category, population densities varied from 0.13 to 0.73 individuals per hectare, being P. pernambucensis the taxa with the lowest, and Hemitriccus g. naumburgae the species with highest population density estimate. Through extrapolation of the observed densities, it was possible to produce minimum population sizes estimates for these birds. Two of these taxa, belonging guild of the of the forest understory insectivorous passerines, also had their microhabitat preferences analyzed. For both, microhabitat selection was based on characteristics of the forest understory vegetation, indicating the importance of microhabitat heterogeneity.